(untitled) (Aporte Santiaguino, 2023)
The aim of the study was to compare the morphometry of adult specimens of the grasshopper Taeniopoda varipennis Rehn, 1905 (Orthoptera: Romaleidae), collected in Chiriquí, Panama. Materials obtained from David, Boquerón, Alanje and Bugaba districts were reviewed. The variables considered were length of the body, antenna, femur, tibia and pronotum, height of the pronotal crest and width of the pronotum. Thirty-two male specimens were selected for a K mean cluster analysis with five pre-established groups; using an online statistical application. According to the results, group 1 stood out with specimens of 5.0-5.3 cm in body length, although all the materials evaluated were close to what was described for the species. Among the factors that could influence the analyzed variables, are the climatic conditions and the available food, because although in the places from which larger specimens were obtained there are various crops, in other locations of the country a preference of the insect has been observed for reproducing and feeding on Crinum amabile plants, of which medicinal properties have been reported. In conclusion, the morphometric analysis highlighted a group of T. varipennis males, but it is necessary to continue investigating its ecology, behavior and possible alternatives for use.